Documents on the confederation of British North America : a compilation based on Sir Joseph Pope's Confederation documents supplemented by other official material - Ajzenstat, Janet, 1936-; Browne, G. P. (Gerald Peter) (Carleton library, 2009)
Presents John A Macdonald's records of the process by which the Fathers of Confederation drafted the Canadian Constitution and prepared it for passage by the Westminster Parliament. This title is augmented by a selection of letters, notes from informal meetings, and colonial office memoranda.